2021
DOI: 10.1111/jce.14896
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of intraprocedural integration of cardiac CT to guide left ventricular lead implantation for CRT upgrades

Abstract: Background Optimal positioning of the left ventricular (LV) lead is an important determinant of cardiac resynchronization therapy (CRT) response. Objective Evaluate the feasibility of intraprocedural integration of cardiac computed tomography (CT) to guide LV lead implantation for CRT upgrades. Methods Patients undergoing LV lead upgrade underwent ECG‐gated cardiac CT dyssynchrony and LV scar assessment. Target American Heart Association segment selection was determined using latest non‐scarred mechanically ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 22 publications
(51 reference statements)
1
27
0
Order By: Relevance
“…Despite 30 years of clinical development, no single definition of CRT response has been universally accepted [4]; however, ≥15% reduction in LV ESV is the most commonly used [2], [8] and can be measured with great precision using 4DCT. Previous studies using CT to guide CRT have used echocardiography derived LV ESV to determine response [16], [27]; however, the reproducibility of the echocardiography measures is low causing uncertainty in the results. The image-based response definition used in this study was derived from the LV blood volume segmentations of the baseline and the follow-up 4DCT images, which are highly reproducible [28] and are free from any assumptions about LV geometry or manual contouring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite 30 years of clinical development, no single definition of CRT response has been universally accepted [4]; however, ≥15% reduction in LV ESV is the most commonly used [2], [8] and can be measured with great precision using 4DCT. Previous studies using CT to guide CRT have used echocardiography derived LV ESV to determine response [16], [27]; however, the reproducibility of the echocardiography measures is low causing uncertainty in the results. The image-based response definition used in this study was derived from the LV blood volume segmentations of the baseline and the follow-up 4DCT images, which are highly reproducible [28] and are free from any assumptions about LV geometry or manual contouring.…”
Section: Discussionmentioning
confidence: 99%
“…Rinaldi and colleagues utilized 4DCT-derived assessment of LV dyssynchrony and myocardial scar to target LV lead placement. They showed that patients with leads implanted in segments targeted from CT had higher clinical response rates [15] and superior acute hemodynamic responses [16] than those with leads implanted in the non-target segments. Fyenbo et al used CT to identify regions of myocardial scar and to compute scar burden.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier image-guided LVLP studies used the 16-segment American Heart Association models. 11 , 12 , 13 By contrast, we incorporated a more specific 36-segment model, which allowed us to differentiate between more segments deemed relevant for LVLP. A predefined decision model was used to assist clinical decision making and improve reproducibility and user independence of target selection for LVLP.…”
Section: Methodsmentioning
confidence: 99%
“…Randomized trials have demonstrated superior CRT response and lower mortality and hospitalizations for heart failure when an echo-guided approach is used to target the LV lead to the site of the latest mechanical activation [ 6 , 7 ]. Small pilot studies of magnetic resonance imaging-guided and computed tomography-guided LV lead placement have demonstrated the additional benefits of avoiding areas of myocardial scar [ 8 , 9 ]. More recently, the international multicenter RADI-CRT trial demonstrated superior LV remodeling when a pressure wire was used to choose the optimal coronary sinus branch based on acute hemodynamic response [ 10 ].…”
Section: Potential Advantages Of Left Ventricular Endocardial Pacingmentioning
confidence: 99%